2013
DOI: 10.1590/s0365-05962013000200023
|View full text |Cite
|
Sign up to set email alerts
|

Polarized dermoscopy of mammary Paget disease

Abstract: Mammary Paget's disease is a rare intraepithelial adenocarcinoma, located on the nipple/areola complex, highly associated with breast cancer. Although the international literature emphasizes the dermatoscopic pattern of mammary Paget's disease pigmented variant, the authors describe the dermoscopic findings of classical Paget's disease and demonstrate the presence of chrysalis-like structures, criteria recently described in the literature and not yet reported in Paget's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…In order to facilitate the differentiation from other skin diseases, we summarized the dermoscopic differential diagnosis of BD in Table 2, including SK, BCC, AK, MM, LPLK, MPD, and LMM. 12,[14][15][16][17][18] In conclusion, BD is an in situ epithelial carcinoma showing various clinical manifestations and dermoscopic features. This study involved a larger number of cases including both pigmented and nonpigmented BD, systematically analyzed the dermoscopic features of BD, and proposed two new dermoscopic findings relatively specific for BD.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to facilitate the differentiation from other skin diseases, we summarized the dermoscopic differential diagnosis of BD in Table 2, including SK, BCC, AK, MM, LPLK, MPD, and LMM. 12,[14][15][16][17][18] In conclusion, BD is an in situ epithelial carcinoma showing various clinical manifestations and dermoscopic features. This study involved a larger number of cases including both pigmented and nonpigmented BD, systematically analyzed the dermoscopic features of BD, and proposed two new dermoscopic findings relatively specific for BD.…”
Section: Resultsmentioning
confidence: 92%
“…Since BD shares some dermoscopic features with SK, BCC, etc., it is hard to define a dermoscopic algorithm for BD. In order to facilitate the differentiation from other skin diseases, we summarized the dermoscopic differential diagnosis of BD in Table , including SK, BCC, AK, MM, LPLK, MPD, and LMM …”
Section: Discussionmentioning
confidence: 99%
“… 31 In 2013, Crignis et al made a dermoscopic study of polarized light in a classic case of MPD (non-pigmented) and found the presence of "chrysalis-like" structures, a feature described lately in the literature but not yet reported in MPD cases. 32 One study was recently published on the use of confocal microscopy in 10 patients with MPD and EMPD, with satisfactory results. 33 …”
Section: Diagnosismentioning
confidence: 99%
“…4,5,6 Dermoscopic features may be found even in the classic (clinically non-pigmented) form of mammary Paget's disease including light brown diffuse pigmentation, irregular black dots, irregularly distributed blue-tray dots (peppering), and irregular linear vessels; moreover, several chrysalis -like structures may additionally be detected. 7,8 The shiny white streaks, originally termed chrysalislike structures, reveal shiny, bright white and linear streaks that can only be visualised with polarised light dermoscopy. These lines represent new or remodelled collagen bundles and are generally oriented parallel or orthogonally to each other.…”
Section: Discussionmentioning
confidence: 99%